Gene-Nutrient Interactions in G6PD-Deficient Subjects – Implications for Cardiovascular Disease Susceptibility - Muntoni, Sergio; Muntoni, Sandro (Journal of nutrigenetics and nutrigenomics, 2008)
Background/Aims: The enzyme glucose-6-phosphate dehydrogenase (G6PD) is the principal source of reducing equivalents, necessary for regenerating reduced glutathione through NADPH in order to protect cells from oxidative damage, and whichin erythrocytes produces hemolysis. When fava beans are ingested by G6PD-deficient subjects (gene-nutrient interaction), or some oxidant drugs are assumed (gene-drug interactions), a life-threatening hemolysis can occur. However, the same defect results in lower cardiovascular disease (CVD) risk. Methods: Physiopathological, clinical and mortality studies of CVD risk in relation with G6PD deficiency have been surveyed. Results: CVD risk in men was lowered in the G6PD-deficient state, and was associated with reduced levels of plasma low-density lipoprotein cholesterol (LDL-C) compared to the normal condition (p < 0.05). Both cholesterol and DNA synthesis in circulating mononuclear cells from G6PD-deficient men were likewise reduced (p = 0.05). Conclusions: Since NADPH is a necessary cofactor for the enzyme 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMG-CoA R), G6PD deficiency appears to be a naturally occurring model of HMG-CoA R restraint, whose consequences are similar to those produced on the same enzyme by statins. G6PD deficiency therefore results in protection against CVD, despite an increased susceptibility to oxidative stress.